2022
DOI: 10.1017/rdc.2022.80
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Inter-Comparison Tests of the Micadas at the Radiocarbon Laboratory of Lanzhou University, China

Abstract: Since 2018, the radiocarbon laboratory of Lanzhou University has been equipped with a compact accelerator mass spectrometer—a 200-KV mini carbon dating system (MICADAS), together with an auto graphitization equipment (AGE III). The laboratory has for a long time prepared graphite targets for 14C dating of plant fossils, charcoal, bones, and bulk organic matter. Herein, we give an overview of the operating status and performance of the dating facility. The long-term measurements of the standard and blank sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Eighteen collagen samples were selected for the radiocarbon dating; they were graphitized with Automated Graphitization Equipment (AGE III) and measured by a compact Accelerator Mass Spectrometer (MICADAS) at the Key Laboratory of Western China's Environmental Systems (Ministry of Education), Lanzhou University (Cao et al, 2023). The 14 C dates were calibrated to calendar age by the online program, OxCal 4.4 version (Ramsey, 2009) based on the IntCal20 curve (Reimer et al, 2020) and reported as “cal AD.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen collagen samples were selected for the radiocarbon dating; they were graphitized with Automated Graphitization Equipment (AGE III) and measured by a compact Accelerator Mass Spectrometer (MICADAS) at the Key Laboratory of Western China's Environmental Systems (Ministry of Education), Lanzhou University (Cao et al, 2023). The 14 C dates were calibrated to calendar age by the online program, OxCal 4.4 version (Ramsey, 2009) based on the IntCal20 curve (Reimer et al, 2020) and reported as “cal AD.”…”
Section: Methodsmentioning
confidence: 99%
“…The bone collagen was extracted according to the method described by Richards and Hedges (1999) Systems (Ministry of Education), Lanzhou University (Cao et al, 2023).…”
Section: Radiocarbon Datingmentioning
confidence: 99%
“…A tree branch sample unearthed from the SDNBT site was prepared according to the standard acid-alkali-acid pre-treatment method similar to that described by Cao et al [27]. The sample was then graphitised and analysed in an accelerator mass spectrometer (AMS) at the Key Laboratory of Western China's Environmental Systems, Lanzhou University.…”
Section: Radiocarbon Datingmentioning
confidence: 99%
“…AMS radiocarbon dating was carried out at the Key Laboratory of Western China's Environmental Systems (Ministry of Education) in Lanzhou University using an MICA-DAS system. Details about the laboratory and the relevant protocols were reported in a recent paper [52]. The OxCal 4.4.4 program and the IntCal20 calibration curve were used in this study to calibrate the original radiocarbon dates [53][54][55].…”
Section: Radiocarbon Datingmentioning
confidence: 99%